2020
DOI: 10.3390/en13225858
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Charging Strategies for Electric Vehicles in an Austrian Office Site

Abstract: Electric vehicles represent a necessary alternative for wheeled transportation to meet the global and national targets specified in the Paris Agreement of 2016. However, the high concentration of electric vehicles exposes their harmful effects on the power grid. This reflects negatively on electricity market prices, making the charging of electric vehicles less cost-effective. This study investigates the economic potential of different charging strategies for an existing office site in Austria with multiple ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This article will calculate revenues to show that aggregated V2G DERs can earn significant revenue from providing grid services. The present work differs from recent V2G studies, for example, Aparicio and Grijalva [3] and Corinaldesi et al [4], as our model calculates value across multiple markets and policy conditions: controlled charging and bidirectional arbitrage at the retail level, plus regulation in wholesale markets, the latter assuming RTO policies to comply with FERC Order 2222. Our formulas also calculate the effect of the policy variable of retail net energy metering (NEM) if offered when discharging to the grid.…”
Section: Introductionmentioning
confidence: 89%
“…This article will calculate revenues to show that aggregated V2G DERs can earn significant revenue from providing grid services. The present work differs from recent V2G studies, for example, Aparicio and Grijalva [3] and Corinaldesi et al [4], as our model calculates value across multiple markets and policy conditions: controlled charging and bidirectional arbitrage at the retail level, plus regulation in wholesale markets, the latter assuming RTO policies to comply with FERC Order 2222. Our formulas also calculate the effect of the policy variable of retail net energy metering (NEM) if offered when discharging to the grid.…”
Section: Introductionmentioning
confidence: 89%
“…Based on the current legal situation in Poland, K. Zagrajek analyzed the feasibility of V2G technology participation in the Polish electricity market and proposed a business model [22]. C. Corinaldesi examined the economic impact of different charging strategies on EVs and concluded that implementing rational charging strategies can enhance economic efficiency [23]. M. Incia suggested that EVs can be aggregated into virtual power plants (VPPs), enabling the implementation of V2G technology's business schemes [24].…”
Section: Conceptmentioning
confidence: 99%
“…Further complementing our approach, ref. [20] outlines the economic impacts and advantages of various EV charging strategies, emphasizing smart grid integration and the benefits of reduced operational costs through optimized charging processes. Ref.…”
Section: Main Contributionsmentioning
confidence: 99%